Women and corporate leadership: exploring the gender gap at the top - Mateos de Cabo, Ruth (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2017)
The persistence of a gender gap in corporate leadership positions is a major socio-economic challenge, as gender inequalities in the labor market in general, and in high decision-making positions in particular, not only suffocate the social development but hurts economic growth. Although previous research has helped to place the issue of the small number of women in leadership on the agenda for both practitioners and policy makers, knowledge is still fragmented without systematically addressing possible causes of inequality in the highest corporate positions. In addition, the studies examining instruments to promote women’s leadership often assume particular barriers that women face and do not link the different causes of inequality with nuanced policy tools and policies to fight them. Therefore, this research goal is to shed light on the reasons why barriers preventing gender equality at the top corporate levels exists, studying and proposing specific policy measures to promote women careers. The paper concludes analyzing the accelerated progress on women representation on corporate leadership positions driven by political and regulatory pressure in a few Member States of the 28 EU countries and offering a series of suggestions to progress women presence on corporate boards.